Arctic Art & Culture - Ignatieva, S.; Kharlampieva, N.; Azheeva, E.; Nikiforova, V.; Maximova, S. (The Arctic State Institute of Culture and Arts (ASICA), 2023)
The popular science journal includes the materials about educational, research, scientific and practical activity of the team from the Arctic State Institute of Culture and Arts and the Northern Forum regions facilitating the image-making of the North and Arctic.